Prominent Intracytoplasmic Crystals in Alveolar Soft Part Sarcoma (ASPS): An Aid in Cytological Diagnosis - Mannan, Rahul (JCDR Research and Publications (P) Limited, 2014)
Alveolar soft part sarcoma (ASPS) is a rare neoplasm of unknown histogenesis with poor prognosis. Due to the epithelioid appearance of the neoplastic cells, ASPS may resemble many neoplastic conditions, such as metastatic epithelial cell tumours with clear cell change, metastatic renal cell carcinoma, granular cell tumour, epithelioid sarcoma, malignant melanoma and even paragangliomas. Presence of abundant, rod like crystals in the cytoplasm of tumour cells is an important finding characteristic of this tumour, which helps in differentiating it from the other entities. The case study highlights the importance of correlating cytological features that help in reaching the diagnosis such as the background, cell morphology and presence of characteristic rod shaped crystals as immunohistochemical studies are often non-conclusive. The case also is unique as it demonstrates presence of intra-cytoplamic crystals in such abundance.